Case report: Early molecular confirmation and sodium polystyrene sulfonate management of systemic pseudohypoaldosteronism type I - Alkhatib, Einas H.; Bartlett, Deirdre; Kanakatti Shankar, Roopa; Regier, Debra; Merchant, Nadia (Frontiers in Endocrinology, 2024)
Introduction Type 1 pseudohypoaldosteronism (PHA) consists of resistance to aldosterone. Neonatal presentation is characterized by salt wasting, hyperkalemia, and metabolic acidosis with high risk of mortality. Type 1 PHA can be autosomal dominant (renal type 1) or autosomal recessive (systemic type 1). Renal PHA type 1 can be feasibly managed with salt supplementation; however, systemic PHA type 1 tends to have more severe electrolyte imbalance and can be more refractory to treatment. Case Presentation We present a case of a 3-year-old girl with systemic PHA type 1, diagnosed and confirmed molecularly in infancy, who has been successfully managed with sodium polystyrene sulfonate decanted into feeds along with sodium supplementation. On day 5 of life, a full-term female infant presented to the ED for 2 days of non-bloody, non-bilious emesis, along with hypothermia to 94°F. Laboratory results were notable for hyponatremia (Na) of 127, hyperkalemia (K) of 7.9, and acidosis with bicarbonate level of 11.2. Genetic testing ordered within a week of life confirmed PHA type 1 with a homozygous pathogenic frameshift variant in SCNN1A c.575delA (p.Arg192GlyfsX57). Sodium polystyrene sulfonate and feeds were decanted until the age of 16 months, and she was also continued on NaCl supplementation. She was gradually transitioned to directly administered sodium polystyrene sulfonate without any electrolyte issues. She has overall done well after gastrostomy-tube (G-tube) placement without severe hyperkalemia even with several hospitalizations for gastrointestinal or respiratory illnesses. Discussion/Conclusion A treatment approach to systemic PHA and sodium polystyrene sulfonate administration in neonates and infants is described.